Karakterisasi dan Kepadatan Bakteri Nitrifikasi pada Tingkat Kematangan Tanah Gambut yang Berbeda Di Kawasan Hutan Lindung Gunung Ambawang Kabupaten Kubu Raya - Riza Linda, Agustina Kiding, Siti Khotimah, (Universitas Tanjungpura, 2015)
Nitrifying bacteria has an important role in oxidizing ammoniac to be nitrit which is required by plants. The purpose of this study is to investigate character and density of nitrifying bacteria at maturity level of peat soil. The sampel was taken at wildlife sanctuary of Ambawang mountain Kubu Raya district. The proses of isolation was conducted by pour plate method that applying spesific media of nitrification and total plate account was used to calculate the density of bacteria. Observation and identification was implemented macroscopically, microscopically and biochemically. The finding indicated that 5 genus of nitrifying bacteria had different level of maturity in peat soil. Nitrosomonas, Nitrobacter and Nitrosococcus were some types ofbacteria that were pound in fibrik meanwhile in hemik, Nitrobacter and Nitrosocystis were identified. In addition, in saprik, Nitrobacter, Nitrospina and Nitrosococcus were discovered. The total density of nitrifying bacteria colonies in maturity level of peat soil in fibrik, hemik and saprik was 160 x 105 CFU/g, 107,5 x 105 CFU/g, and 19 x 105 CFU/g.